A developmental study of the effect of music training on timed movements - Braun Janzen, Thenille; Thompson, William F.; Ranvaud, Ronald (Frontiers in Human Neuroscience, 2014)
When people clap to music, sing, play a musical instrument, or dance, they engage in temporal entrainment. We examined the effect of music training on the precision of temporal entrainment in 57 children aged 10–14 years (31 musicians, 26 non-musicians). Performance was examined for two tasks: self-paced finger tapping (discrete movements) and circle drawing (continuous movements). For each task, participants synchronized their movements with a steady pacing signal and then continued the movement at the same rate in the absence of the pacing signal. Analysis of movements during the continuation phase revealed that musicians were more accurate than non-musicians at finger tapping and, to a lesser extent, circle drawing. Performance on the finger-tapping task was positively associated with the number of years of formal music training, whereas performance on the circle-drawing task was positively associated with the age of participants. These results indicate that music training and maturation of the motor system reinforce distinct skills of timed movement.